2014
DOI: 10.4071/isom-thp12
|View full text |Cite
|
Sign up to set email alerts
|

Design and Direct Assembly of 2.5D/3D Rigid Silicon Interposer on PCB

Abstract: Silicon interposer is emerging as a vehicle for integrating dies with sub 50um bump pitch in 2.5D/3D configuration. Benefits of 2.5D/3D integration are well explained in the literature, however, cost and reliability is a major concern especially with the increase in interposer size. Among the challenges, reliability issues such as warpage, cracks and thermal-stresses must be managed, in addition, multi-layer build-up flip chip substrate cost and its impact on the overall yield must be considered. Because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Electrical testing before and after temperature cycling experiments showed that temperature cycles of up to 1000 cycles did not cause any open circuits or significantly affect the electrical resistance of the via chains with printed dielectric polymer filling, confirming the findings in Ref. 10. Thus, the difference of the CTEs of Si, Cu, and the dielectric polymer do not appear to affect the electrical functionality of the TSVs.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Electrical testing before and after temperature cycling experiments showed that temperature cycles of up to 1000 cycles did not cause any open circuits or significantly affect the electrical resistance of the via chains with printed dielectric polymer filling, confirming the findings in Ref. 10. Thus, the difference of the CTEs of Si, Cu, and the dielectric polymer do not appear to affect the electrical functionality of the TSVs.…”
Section: Resultssupporting
confidence: 75%
“…It was also demonstrated that solder balls can be printed successfully on the interposers, thereby demonstrating the potential for a four-times increased I/O density compared to the same TSV platform used in Ref. 10 but without filling of the hollow vias with the dielectric polymer. …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations